PERANCANGAN GAME ACTION ROLE PLAYING TOWER DEFENSE “TRIBAL DEFENDERS” - Kenneth Hakim; Darius Andana Haris; Viny Christanti Mawardi (Fakultas Teknologi Informasi Universitas Tarumanagara, 2016)
“Tribal Defenders” is a game with a hybrid of two genres: Action Role Playing Game and Tower Defense, posessing goal of entertaining players aged teens and above. Players are allowed to choose one of two characters provided as the main character. As of the usual tower defense games, players are given a task of defending an object using towers. However as a hybrid of action role playing game and tower defense, players are given abilities to enter the combat such as attacking and using skills with the selected character. Player also given access to character status customization as the character will level up and gain status points from each stage. The game was made with unity using C# as the programming language, as for the art and design was made with PaintTool Sai and Adobe Photoshop Cs6. Alpha testing of the game is done by the mentors, while the beta testing is done by allowing a number of users play the game and review it by filling questionnaire provided after. The result shows that the genre of “Tribal Defenfers” are somewhat new to users and majority of users find the “Tribal Defenders” are enjoyable.